(3GddLGf GdeJNUUI ai efGRYGJ GdJGejf GdGLJeGYi ai eUQ (B: s (3Hjf GdfU h GdJWHjb (B/ s - (3UGHQ eMeO Ydi YHOGdQMjes; (3GMeO MSf GdHQYj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3HGdJYQV ai GdaUd GdJegjOi dgjFGJ GdJGejf GdGLJeGYi ai eUQ (B: (3hJWhQgG (B0 (3Ke YQVfG ai GdHGH GdGhd (B: (3ddGSHGH GdJi JDOi Gdi fThH GdfRGY Hjf GUMGH GdTGf (B: (3hGdgjFI GdJGejfjI GdeNJUI (B: (3hYhGFb GdJWHjb GdYedi dbGfhf GdJGejf GdGLJeGYj (B: (3h GhVMfG Gf Gge gPg GdYhGFb (B: (3JbGYS GdYGedjf HGdgjFI (B: (3Gh UGMH GdYed (B: (3Gh GdYGedjf ai GdLgGJ GdGOGQjI (B: (3Gh GLgRI GdQbGHI GdOGNdjI HGdgjFI GdJGejfjI GdeNJUI (B: (3Yf GOGA GdOhQ GdPi GfGWge GdbGfhf (B0 (3hJYQVfG ai GdHGH GdKGfi Gdi GdWHjYI GdbGfhfjI dJdc GddLGf (B: (3hGfJgjfG Gdi GfgG dG JYOh Gf Jchf dLGf GOGQjI (B: (3GdgOa efgG eLQO eMGhdI JShjI GdfRGY HGdWQb GdhOjI (B: (3hGfgG JMJGL ef GdeTQY Gdi GdJONd (B: (3HGYGOI JfXjegG (B: (3Ydi fMh JfXjeg ddLGf GdJhajbs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2006s
(3HHdjhLQGajG(B: (3UaMGJ (B269-274s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GSHGH GdfRGYs; (3GdWHjYI GdbGfhfjIs; (3GdgjFGJ GdJGejfjIs; (3GdJCejf GdGLJeGYj HeUQs; (3GdUfGOjbs; (3GdgjFI GdbhejI ddJCejf GdGLJeGYjs; (3GddLGf GdeJNUUIs; (3GdGTJQGcGJ GdJGejfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs